A laboratory method for evaluating fungicides against Uncinula necator - CHANDER MOHAN, T.S. THIND and (Indian Phytopathology, 2002)
The methods being currently employed for testing fungicides against Uncinula necator (Schw.) Burr, involve inoculations of the fungicide-treated leaf surface coated glass slides or touching against the sporulating colonies on the already infected plants. However, these may lead to erroneous results due to uneven deposition of inoculum on the treated surface and the difficulty encountered while taking observations, due to clumping of conidial chains/conidia at one spot, Further, utilisation of separate leaves for different treatments may also give misleading information because of their varied sensitivity response to U. necator. Keeping this into view, a laboratory technique has been developed to overcome these problems.